Patterns of emergent resistance-associated mutations after initiation of non-nucleoside reverse-transcriptase inhibitor-containing antiretroviral regimens in Taiwan: a multicenter cohort study - Cheng, Chien-Yu (Infect Drug Resist, 2018)
BACKGROUND: Increasing trends of resistance-associated mutations (RAMs) to non-nucleoside reverse-transcriptase inhibitors (nNRTIs) have raised concerns about the effectiveness of the regimens in the national HIV treatment programs in resource-limited countries. We aimed to retrospectively investigate the incidence and patterns of emergent RAMs of HIV-1 in HIV-positive adults experiencing virological failure to first-line nNRTI-containing combination antiretroviral therapy (cART) in Taiwan. PATIENTS AND METHODS: Between June 2012 and March 2016, 1138 antiretroviral-naïve HIV-positive adults without baseline RAMs who initiated nNRTI-containing regimens were included for analysis. Virological failure was defined as plasma viral load (PVL) ≥200 copies/mL after 6 months of cART or confirmed PVL ≥200 copies/mL after achieving PVL <50 copies/mL. Population sequencing was retrospectively performed to detect baseline and emergent RAMs. RAMs were interpreted using the International AIDS Society-USA 2016 mutations list. RESULTS: Seventy-one patients (6.2%) developed virological failure, which occurred in 14.8% (43/291), 3.9% (26/675), and 1.2% (2/172) of patients receiving 2 nucleoside reverse-transcriptase inhibitors (NRTIs) plus nevirapine, efavirenz, and rilpivirine, respectively. Among those, 53 (74.6%) had emergent RAMs identified, which included 43 (81.1%), 53 (100.0%), and 1 (1.9%) with RAMs to NRTIs, nNRTIs, and protease inhibitors, respectively; and 43 (81.1%) had multi-drug resistance. The most common emergent RAMs to NRTIs were M184V/I (42.3%) and K65R (28.2%), and those to nNRTIs were Y181C (42.3%), K103N (15.5%), G190A/E/Q (12.7%), V179D/E (12.7%), and V108I (9.9%). CONCLUSION: While the rates of virological failure varied with the nNRTI used, the rate of emergent RAMs of HIV-1 to NRTIs and nNRTIs among the antiretroviral-naïve patients who failed nNRTI-containing cART remained low.